2001
DOI: 10.1007/s004240100014
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative and apoptotic activity in hepatocellular carcinoma and surrounding non-neoplastic liver tissue

Abstract: PCNA and Ki-67 were useful for proliferative activity assessment of hepatocytes. There were no differences in apoptotic activity between HCC and non-neoplastic tissue, so it seems that uncontrolled tumour cell division plays an important role in HCC growth. In the regulation of the apoptotic process in HCC, Bcl-2 could be important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 5 publications
3
21
0
Order By: Relevance
“…The median tumor size was 4.5 cm (range 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; the mean tumor size 5.574.4 cm. In total, 72% of the hepatocellular carcinoma were solitary tumors, 28% multiple.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median tumor size was 4.5 cm (range 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]; the mean tumor size 5.574.4 cm. In total, 72% of the hepatocellular carcinoma were solitary tumors, 28% multiple.…”
Section: Resultsmentioning
confidence: 99%
“…13 Thus, mean proliferation labeling index (Ki-67, Proliferation Cell Nuclear Antigen) is shown to correlate significantly with survivin, whereas apoptotic index (single-stranded DNA immunohistochemistry, Tunel) does not. [13][14][15][16] This suggests that, as in hepatocellular carcinoma, the prognostic significance in other cancers of survivin immunostain in nuclei relates to its cell cycle, and not to its cytoplasmic antiapoptotic, effect. Moon and Tarnawski 32 suggest that cytoplasmic localization of survivin in quiescent nonmalignant cells suppresses apoptosis, while its nuclear translocation in hepatocellular carcinoma may be important in regulation of proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCNA is a protein involved in DNA replication and repair in dividing cells. Ki67 is a prototypic cell cycle-related nuclear protein expressed only in proliferating cells [33]. Only the cells in group 1a organs were able to upregulate the expression of both proteins 24 h after resection as shown in Figs.…”
Section: Discussionmentioning
confidence: 95%
“…These differences reflect probably sampling errors and size of the biopsies, but they do not seem to indicate a significant difference between the results [4]. Recent studies also suggested that apoptosis is slightly higher in HCC as compared to normal liver, which implies that it is less involved in the development and progression of this disease [11][12][13]. Thus, although a high index of proliferation seems to be characteristic for HCC, this is not associated with an increased rate of apoptosis.…”
Section: Discussionmentioning
confidence: 99%